2017
DOI: 10.7759/cureus.1797
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion Thresholds Among Children Admitted to a Pediatric Intensive Care Unit

Abstract: ObjectiveTo evaluate the threshold for platelet transfusion in children admitted to a pediatric intensive care unit (PICU). This is a retrospective chart review study, conducted at our tertiary level PICU and is related to critically ill pediatric patients who required platelet transfusion.MethodsWe retrieved the target patient population data from our blood bank database. The patients were subdivided into four subgroups: hematologic (hematologic malignancies, bone marrow suppression, hemolytic anemia, and sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There is a wide variation in the practice of prophylactic platelet transfusion in children, and most of the clinical practice guidelines are based on expert opinion. Often the platelet count threshold for transfusion varied depending on the geographic location of clinical practice (29), with underlying clinical indication and diagnosis (4,5,64,65). The clinical practice of platelet transfusion for hypoproliferative thrombocytopenia cannot be applicable in thrombocytopenia due to immune-mediated platelet destruction.…”
Section: Prophylactic Platelet Transfusionmentioning
confidence: 99%
“…There is a wide variation in the practice of prophylactic platelet transfusion in children, and most of the clinical practice guidelines are based on expert opinion. Often the platelet count threshold for transfusion varied depending on the geographic location of clinical practice (29), with underlying clinical indication and diagnosis (4,5,64,65). The clinical practice of platelet transfusion for hypoproliferative thrombocytopenia cannot be applicable in thrombocytopenia due to immune-mediated platelet destruction.…”
Section: Prophylactic Platelet Transfusionmentioning
confidence: 99%
“…7 There has been limited data about evidence-based guidelines regarding platelet transfusion in the paediatric age group and this may end up in transfusing at a wide range of thresholds with reference to studies conducted on the adult population. 1,8 Blood transfusions should be done judiciously keeping in view their scarcity and significance in health care facilities and minimizing the risks associated with transfusions. Although several countries have developed guidelines for effective blood transfusion practices, there is still a significant rate of inappropriate transfusions being done globally.…”
Section: Introductionmentioning
confidence: 99%
“…An observational study of 405 children reported that 9% experienced clinically relevant bleeding, and platelets were transfused in 16% with a median (IQR) platelet count 181 × 10 9 /L (108–257 × 10 9 /L)(36). Oncology patients represent a common cohort of patients who receive platelet transfusions in the PICU (2, 37). A recent point prevalence study of platelet transfusion practice of 237 inpatient PICU oncology patients found that 30% of transfusions were administered for therapeutic indications (major bleeding 9%, minor bleeding 16%) at a median (IQR) pretransfusion platelet count of 56 × 10 9 /L (37–89 × 10 9 /L) and that 60% were administered prophylactically at thresholds of greater than 20 × 10 9 /L (2).…”
Section: Resultsmentioning
confidence: 99%